Measurement of vocational competencies - a contribution to an international large-scale assessment on vocational education and training - Winther, Esther [Verfasser]; Achtenhagen, Frank [Verfasser] (My University, 2009)
"Measurement of vocational competencies which includes not only the knowledge but also the action domain is one of the central targets of VET research - under scientific as well political perspectives. It also is a decisive prerequisite for running an international large-scale assessment on VET. The article describes how such measurement is operationalized by defining dimensions of VET competencies and developing adequate items which mirror authenticly tasks to be fulfilled at the workplace. Tasks and items are presented in the context of a technology-based virtual enterprise focusing on the fields of business and administration. Their format allows Item Response Theory (IRT) scaling." (Autorenreferat, BIBB-Doku)
Keywords: L 6.3.1 Diagnose- & Messinstrumente; L 8 Diagnostik / Eignung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Berufsbildung; Kaufmännische Ausbildung; Kompetenzfeststellung; Kompetenzbewertung; Berufsbildungs-PISA; Europäischer Qualifikationsrahmen